Scanning near-field optical microscopy of magnetic structures in magnetic films - Belotelov, V.I.; Logginov, A.S.; Nikolaev, A.V.; Pyatakov, A.P.; Zvezdin, A.K. (Functional Materials, 2004)
Magnetooptical observation of magnetic domain walls in iron-garnet films by scanning near field optical microscopy has been studied to reveal the advantages of the near-field imaging in terms of spatial resolution. Recent experiments have shown that in case of 5 to 10 μm thick magnetic films, near field observation of domain structures does not provide obvious spatial resolution increase as compared to the conventional optical microscopy. Theoretical analysis based on the Green functions method revealed that the film thickness plays a crucial role in this effect. Qualitative explanation of the resolution deterioration with the increasing film thickness is also given.